Occupational exposure to diesel and gasoline emissions and lung cancer in Canadian men. - Villeneuve, Paul J; Parent, Marie-Élise; Sahni, Vanita; Johnson, Kenneth C; Group, The Canadian Cancer Registries Epidemiology Research (Environmental Research, 2011)
The Canadian Cancer Registries Epidemiology Research Group comprised a principal investigator from each of the provincial cancer registries involved in the National Enhanced Cancer Surveillance System: Bertha Paulse, Newfoundland Cancer Foundation; Ron Dewar, Nova Scotia Cancer Registry; Dagny Dryer, Prince Edward Island Cancer Registry; Nancy Kreiger, Cancer Care Ontario; Erich Kliewer, Cancer Care Manitoba; Diane Robson, Saskatchewan Cancer Foundation; Shirley Fincham, Division of Epidemiology, Prevention and Screening, Alberta Cancer Board; and Nhu Le, British Columbia Cancer Agency. International audience The International Agency for Research on Cancer classifies diesel exhaust as a probable human carcinogen; this decision is based largely from lung cancer evidence. Gasoline exhaust is classified as a possible carcinogen. Epidemiological studies are needed that improve upon some of the limitations of previous research with respect to the characterization of exposure, and the control for the potential confounding influence of smoking and other occupational exposures. Our objective was to investigate associations between occupational exposure to diesel and gasoline engine emissions and lung cancer. We used a case-control study design that involved men 40 years of age and older at the time of interview. Analyses are based on 1681 incident cases of lung cancer and 2,053 population controls. A self-reported questionnaire elicited a lifetime occupational history, including general tasks, and information on other potential risk factors. Occupational exposures to diesel and gasoline emissions, crystalline silica, and asbestos were assigned to each job held by study subjects by industrial hygienists who were blind to case-control status. Exposure metrics for diesel and gasoline emissions that were modeled included: ever exposure, cumulative exposure, and concentration of exposure. We found a dose-response relationship between cumulative occupational exposure to diesel engine emissions and lung cancer. This ...